Integration of product and process approaches in ESL classrooms - Thulasi Palpanadan, Sarala; Ravana, Venosha
English as a second language (ESL) writing instructions demand a great deal of the teachers’ time and effort to prepare adequate writing lessons for their students. Teachers have to decide on the right approach to be selected as the instructional method to enhance students’ writing ability. Thus, this study investigates the preferred teaching practices (between the product and process approach) of 10 pre-service teachers’ in teaching writing and the effects on students’ written texts. The data were collected from observations, semi-structured interviews and students’ written texts. The data from the observation checklists were analyzed using Rasch Measurement Model which validated the study with a high value of alpha Cronbach (0.81). Thematic and textual analyses were conducted on participants’ views and the students’ written text respectively. The findings highlighted the pre-service teachers preferred to employ product approach as their main writing instruction where the students were found to prepare their written work based on the input provided to them. The students’ written work with linguistic accuracy was mainly focused but the students did not show much creatively. Thus, this study recommends that teachers should integrate process approach strategies into their writing instructions to enhance students’ writing more profoundly in the future.